Obstetric Complications and Psychological Well-being: Experiences of Bangladeshi Women during Pregnancy and Childbirth (Journal of Health, Population and Nutrition, 2012)
Women in developing countries experience postnatal depression at rates that are comparable with or  higher than those in developed countries. However, their personal experiences during pregnancy and  childbirth have received little attention in relation to postnatal depression. In particular, the contribution  of obstetric complications to their emotional well-being during the postpartum period is still not clearly  understood. This study aimed to (a) describe the pregnancy and childbirth experiences among women  in Bangladesh during normal childbirth or obstetric complications and (b) examine the relationship between  these experiences and their psychological well-being during the postpartum period. Two groups of  womenone group with obstetric complications (n=173) and the other with no obstetric complications  (n=373)were selected from a sample of women enrolled in a community-based study in Matlab, Bangladesh.  The experiences during pregnancy and childbirth were assessed in terms of a five-point rating scale  from severely uncomfortable=1 to not uncomfortable at all=5. The psychological status of the women  was assessed using a validated local version of the Edinburgh Postnatal Depression Scale (EPDS) at six weeks  postpartum. Categorical data were analyzed using the chi-square test and continuous data by analysis of  variance. Women with obstetric complications reported significantly more negative experiences during  their recent childbirth [95% confidence interval (CI) 1.36-1.61, p